2019
DOI: 10.1158/0008-5472.can-19-1084
|View full text |Cite
|
Sign up to set email alerts
|

SET Domain–Containing Protein 4 Epigenetically Controls Breast Cancer Stem Cell Quiescence

Abstract: Quiescent cancer stem cells (CSC) play important roles in tumorigenesis, relapse, and resistance to chemoradiotherapy. However, the determinants of CSC quiescence and how they sustain themselves to generate tumors and relapse beyond resistance to chemoradiotherapy remains unclear. Here, we found that SET domain-containing protein 4 (SETD4) epigenetically controls breast CSC (BCSC) quiescence by facilitating heterochromatin formation via H4K20me3 catalysis. H4K20me3 localized to the promoter regions and regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…Our current results suggest SETD4 deficiency leads to BMSCs proliferation without affecting the apoptosis. Very recently, Ye S and colleagues reported SETD4 overexpressed breast cancer stem cells deserved low Ki67 expression when compared with SETD4 low expressed breast cancer stem cells; they concluded SETD4 controls breast cancer stem cell quiescence [6]. Our current research found that SETD4 KO BMSCs retain high cell proliferative potentials, which is consistent with Ye S's report on cell proliferation characteristics.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our current results suggest SETD4 deficiency leads to BMSCs proliferation without affecting the apoptosis. Very recently, Ye S and colleagues reported SETD4 overexpressed breast cancer stem cells deserved low Ki67 expression when compared with SETD4 low expressed breast cancer stem cells; they concluded SETD4 controls breast cancer stem cell quiescence [6]. Our current research found that SETD4 KO BMSCs retain high cell proliferative potentials, which is consistent with Ye S's report on cell proliferation characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…SET domain-containing protein 4 (STED4) is a number of SET gene families that process histone and non-histone methyltransferase activity. Previous reports have revealed that SETD4 over-expression controls cancer cell proliferation [4,5] and the cell quiescence via H4K20me3 catalysis [6,7]. Very recently, SETD4-catalyzed H3K4me1 and H3K4me2 were also documented to be closely associated with the release of inflammatory cytokines in macrophage [8].…”
Section: Introductionmentioning
confidence: 98%
“…By isolating BCSCs based on high flavin content, energetic BCSCs (e-BCSCs) were identified with a higher glycolytic activity and a larger mitochondrial mass (25). On the contrary, quiescent BCSCs (qBCSCs) have been reported based on the epigenetic activities (26). Mesenchymal and epithelial phenotypes of heterogeneous BCSCs have been described contributing to differential chemoresistance (27).…”
Section: Heterogeneity In Bc and Its Influence On Clinical Outcomementioning
confidence: 99%
“…The brine shrimp Artemia Parthenogenetica SETD4 was initially suggested to play a role in methylating histone H4K20 and H3K79 (21), and the human SETD4 protein may have the same activity (35). However, another report failed to identify these sites as SETD4 substrates, and instead suggested H3K4 as the substrate of SETD4 in macrophages (36).…”
Section: Introductionmentioning
confidence: 99%
“…According to the TCGA database, oncogenic fusion of SETD4 was found to be with TMPRSS2 in prostate cancer, with FTCD in invasive ductal carcinoma, with KIAA1958 in serous ovarian cancer, and with B4Galt6 in lung squamous cancer. SETD4 was highly expressed in the quiescent breast cancer stem cell subpopulation of MCF7 cells (35), and an induced Setd4 deletion in adult mice delayed the radiationinduced T-lymphoma development in mice (40).…”
Section: Introductionmentioning
confidence: 99%